Is there increased value in robotic arm-assisted total hip arthroplasty?: a nationwide outcomes, trends, and projections analysis of 4, 699, 894 cases. (1st September 2021) - Emara, Ahmed K.; Zhou, Guangjin; Klika, Alison K.; Koroukian, Siran M.; Schiltz, Nicholas K.; Higuera-Rueda, Carlos A.; Molloy, Robert M.; Piuzzi, Nicolas S.
Abstract : Aims: The current study aimed to compare robotic arm-assisted (RA-THA), computer-assisted (CA-THA), and manual (M-THA) total hip arthroplasty regarding in-hospital metrics including length of stay (LOS), discharge disposition, in-hospital complications, and cost of RA-THA versus M-THA and CA-THA versus M-THA, as well as trends in use and uptake over a ten-year period, and future projections of uptake and use of RA-THA and CA-THA. Methods: The National Inpatient Sample was queried for primary THAs (2008 to 2017) which were categorized into RA-THA, CA-THA, and M-THA. Past and projected use, demographic characteristics distribution, income, type of insurance, location, and healthcare setting were compared among the three cohorts. In-hospital complications, LOS, discharge disposition, and in-hospital costs were compared between propensity score-matched cohorts of M-THA versus RA-THA and M-THA versus CA-THA to adjust for baseline characteristics and comorbidities. Results: RA-THA and CA-THA did not exhibit any clinically meaningful reduction in mean LOS (RA-THA 2.2 days (SD 1.4) vs 2.3 days (SD 1.8); p < 0.001, and CA-THA 2.5 days (SD 1.9) vs 2.7 days (SD 2.3); p < 0.001, respectively) compared to their respective propensity score-matched M-THA cohorts. RA-THA, but not CA-THA, had similar non-home discharge rates to M-THA (RA-THA 17.4% vs 18.5%; p = 0.205, and 18.7% vs 24.9%; p < 0.001, respectively). Implant-related mechanical complications were lower in RA-THA (RA-THA 0.5% vs M-THA 3.1%; p < 0.001, and CA-THA 1.2% vs M-THA 2.2%; p < 0.001), which was associated with a significantly lower in-hospital dislocation (RA-THA 0.1% vs M-THA 0.8%; p < 0.001). Both RA-THA and CA-THA demonstrated higher mean higher index in-hospital costs (RA-THA $18, 416 (SD $8, 048) vs M-THA $17, 266 (SD $8, 396); p < 0.001, and CA-THA $20, 295 (SD $8, 975) vs M-THA $18, 624 (SD $9, 226); p < 0.001, respectively). Projections indicate that 23.9% and 3.2% of all THAs conducted in 2025 will be robotic arm- and computer-assisted, respectively. Projections indicated that RA-THA use may overtake M-THA by 2028 (48.3%) and reach 65.8% of all THAs by 2030. Conclusion: Technology-assisted THA, particularly RA-THA, may provide value by lowering in-hospital early dislocation rates and and other in-hospital metrics compared to M-THA. Higher index-procedure and hospital costs warrant further comprehensive cost analyses to determine the true added value of RA-THA in the episode of care, particularly since we project that one in four THAs in 2025 and two in three THA by 2030 will use RA-THA technology. Cite this article: Bone Joint J  2021;103-B(9):1488–1496.